Type I interferons regulate nitric oxide production in Brucella abortus-activated microglia contributing to neuronal death - Rodríguez, Julia; Guano, Alex D.; Mazzitelli, Ignacio; Dennis, Vida A.; Rodríguez, Ana M.; Giambartolomei, Guillermo H. (Frontiers in Immunology, 2025)
Microglia have a central role in the immunopathogenesis of neurobrucellosis where its activation is a hallmark in this disease. In this study, we present in vitro evidence that type I interferons (IFN) are involved in the activation of microglia during Brucella abortus infection and are necessary to induce neuronal death. Neutralization of type I IFN receptor (IFNAR) on microglia cells completely abrogates neuronal loss in primary co-cultures of neurons/microglia infected with B. abortus or treated with culture supernatants from B. abortus-infected astrocytes. Type I IFN regulate inducible nitric oxide synthase (iNOS) expression, and subsequently nitric oxide (NO) production in microglia by increasing STAT1 expression and phosphorylation. Our results also show that NF-κB and the MAPK signaling pathways, ERK1/2 and p38, are implicated in the secretion of type I IFN induced by the bacterium. Finally, our results indicate that iNOS induction and NO production require activation of both NF-κB and STAT1 transcription factors. This observed molecular mechanism contributes to neuronal death induced by B. abortus-activated microglia and may help explain the neurological signs observed in patients with neurobrucellosis.